THE EFFECTIVENESS OF PAIRS TEACHING IN TEACHING VOCABULARY AT SMA KRISTEN MERCUSUAR KUPANG - Soleman Dapa Taka (Institut Agama Islam Negeri Palopo, 2019)
This research is aimed at finding out the effectiveness of pairs teaching in teaching vocabulary to the tenth grade students at SMA Kristen Mercusuar Kupang. This research used pre-experimental research. The population of this research was the first year students of SMA Kristen Mercusuar Kupang in 2018-2019 academic years. The researcher took one class as a sample of the research. Therefore, the total number of sample was 30 students. The procedure that was used to collect data was vocabulary test. Furthermore, the data of this research was analyzed by using SPSS program version 20. The finding of this research shows that the use of pairs teaching is effective in building students’ vocabulary of the tenth grade students of SMA Kristen Mercusuar Kupang. It was proven by the significant difference between the students’ mean score of pretest and posttest. In pretest, the students’ mean score is 49.33 and the students’ score in posttest is 84.96. Moreover, it also could be seen by the result of p.value 0.000. It means that the use of pairs teaching is effective in teaching vocabulary.